Cross-university dialogues to support multicultural school consultation training. (August 2020) - Newman, Daniel S.; Ingraham, Colette L.
Abstract: There is a growing need for school psychologists to build multicultural knowledge, skills, values, and dispositions to serve increasingly diverse student, teacher, and caregiver populations in schools. The purpose of this study was to investigate the process and outcomes of a cross-university dialogue (CUD) activity for 88 school psychologist trainees enrolled in consultation courses, across three school psychology training programs, over three years. The CUD involved partnering with a peer or peers from another training program, individually and then collaboratively completing a case study activity, and writing a guided reflection exercise. It was intended to support trainees' development of multicultural school consultation (MSC) competency and their application of a MSC framework. Constructivist grounded theory methodology and methods, including several features to enhance trustworthiness, guided the investigation. Four themes emerged from the data: (a) trainees established increased self-awareness and professional identity, (b) trainees made sense of multiple perspectives during CUD interactions, (c) trainees learned from their partners and considered future relevance of MSC, and (d) trainees' learning reflected cross-cutting ecological perspectives, influencing the CUD interaction and learning process at multiple levels. A grounded theory based on the data is described, and implications are drawn for the training and development of MSC competence.